SOFTWARE DEVELOPMENT TECHNOLOGY BASED ON ORGANIZING INDEPENDENT LEARNING FOR STUDENTS - Aysuliu Jaksilikovna, Janabergenova (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study investigates the integration of software development technologies in supporting independent learning and aims to develop a strategic framework that enhances learner autonomy and academic performance. Method: Utilizing a qualitative content analysis approach, the research synthesizes literature and real-world applications of Learning Management Systems (LMS), Artificial Intelligence (AI), cloud computing, blockchain, gamification, and interactive platforms to assess their role in independent learning environments. Results: The findings indicate that LMS provides structured and flexible access to content, AI enables adaptive feedback and personalized learning pathways, cloud computing ensures ubiquitous access to resources, and blockchain secures digital credentialing. Gamification and interactive platforms significantly enhance student motivation and engagement. Novelty: This study offers a comprehensive synthesis of how emerging technologies collectively contribute to independent learning, proposing an integrative model that addresses current gaps in digital education strategies. The proposed framework not only highlights practical implications for educators and policymakers but also underscores the importance of digital equity and readiness for future educational challenges in the 21st century.